Acute exercise alters immune responses in older adults, with extracellular vesicle changes observed in a high-intensity intervention - Garza, Alejandra P.; Morton, Lorena; Motsch, Anna-Lena; Puta, Christian; Stiebler, Marvin; Lading, Yves; Chakrabarty, Sabyasachi; Schreiber, Stefanie; Buzás, Edit I.; Braun-Dullaeus, Rüdiger; Müller, Patrick; Dunay, Ildiko R. (Frontiers in Immunology, 2025)
IntroductionAging is accompanied by immunoscenescence and chronic low-grade inflammation (inflammaging), contributing to age-related diseases. Physical exercise is a potent modulator of immune function and systemic inflammation, yet the effects of acute exercise intensity on immune activation, cytokine dynamics, and extracellular vesicle release in older adults remain incompletely characterized, particularly in a sex-specific context. This study investigated how a single session of acute continuous moderate versus intense exercise modulates immune cell subsets, cytokine levels, and EV profiles in healthy older individuals, with emphasis on sex-based differences.MethodsThirty-three older adults completed either a moderate (n=14, 54-79 years; 60% VO2max, 30 minutes) or an intense cycling bout (n=19, 61-85 years; incremental cardiopulmonary exercise test (CPET) to exhaustion). Peripheral blood was collected at baseline, 30 minutes, and 24 hours post-exercise. Immune cells were analyzed by flow cytometry. EVs were characterized by flow cytometry and nanoparticle tracking analysis, and cytokines were quantified by multiplex assays.ResulsModerate exercise enhanced classical monocyte activation (↑CD86, ↓CX3CR1) without altering cell counts, and selectively elevated IL-6 in females. Intense exercise induced stronger innate immune activation, increasing classical and nonclassical monocytes, CD56bright/CD16low NK cells, and sustained TNFα levels. EVs positive for tetraspanins (CD9, CD63, and CD81) were elevated 24h after intense CPET. Exploratory sex-disaggregated analyses revealed distinct profiles: females had increased CD4+ EVs, while males showed elevated HLA-ABC+ EVs.DiscussionAcute exercise modulates immune responses in an intensity- and sex-dependent manner in older adults. Extracellular vesicle release was assessed only in the high-intensity intervention, where significant changes were observed. These findings support personalized exercise regimens to enhance immune resilience and promote healthy aging.